Audit Pemasaran Dan Analisis Penerapan CRM dalam Industri E-commerce Guna Menilai Efektivitas Fungsi Penjualan pada CV. Adiarko Digital Team - Nisa, Lita Khoirun; Fauziyah, Fauziyah; Suprapto, Fitria Magdalena (STIE Perbankan Indonesia, 2025)
This study aims to analyze the implementation of marketing audits and the application of Customer Relationship Management (CRM) in improving the effectiveness of the sales function at CV. Adiarko Digital Team, an e-commerce company focused on marketing clothing and household products. The research method used is descriptive qualitative, with data collection techniques including observation, documentation, and the distribution of questionnaires to company employees. Data analysis was carried out by applying marketing audit procedures and calculating the levels of CRM implementation and sales effectiveness. The results show that the marketing audit scored 74% (fairly effective), CRM implementation reached 72% (fairly effective), and sales effectiveness was measured at 81% (effective). These findings indicate a positive relationship between marketing strategy, customer relationship management, and the achievement of the company’s sales targets. Keyword: Marketing Audit, Customer Relationship Management (CRM), The Effectiveness Of The Sales Function